Effectiveness of host cell protein removal using depth filtration with a filter containing diatomaceous earth. (6th July 2020) - Nejatishahidein, Negin; Borujeni, Ehsan E.; Roush, David J.; Zydney, Andrew L.
Abstract: The increased cell density and product titer in biomanufacturing have led to greater use of depth filtration as part of the initial clarification of cell culture fluid, either as a stand‐alone unit operation or after centrifugation. Several recent studies have shown that depth filters can also reduce the concentration of smaller impurities like host cell proteins (HCP) and DNA, decreasing the burden on subsequent chromatographic operations. The objective of this study was to evaluate the HCP removal properties of the Pall PDH4 depth filter media, a model depth filter containing diatomaceous earth, cellulose fibers, and a binder. Experiments were performed with both cell culture fluid (CCF) and a series of model proteins with defined pI, molecular weight, and hydrophobicity chosen to match the range of typical HCP. The location of adsorbed (fluorescently labeled) proteins within the depth filters was determined using confocal scanning laser microscopy. Protein binding was greater for proteins that were positively charged and more hydrophobic, consistent with adsorption to the negatively charged diatomaceous earth. The lowest degree of binding was seen with proteins near their pI, which were poorly removed by this filter. These results provide new mechanistic insights into the factors governing the filter capacity and performance characteristics of depth filters containing diatomaceous earth that are widely used in the clarification of CCF.